Effect of self-determined motivation in physical education on objectively measured habitual physical activity : a trans-contextual model - Viciana, Jesús (Array, 2019)
Grounded in the trans-contextual model, the purpose of the present study was to examine the role of self-determined motivation in Physical Education (PE) on self-determined motivation in Physical Activity (PA), PA intention, and accelerometer-measured habitual PA behavior among high-school aged adolescents. A sample of 394 Spanish high-school students (211 males and 183 females; aged 12-16 years) participated in the present study. The outcome measure of PA was established using accelerometry, whereas motivation toward PA and PE as well as PA intention were measured using validated questionnaires. Path analyses supported in part the central propositions of the trans-contextual model. Self-determined motivation in PE predicted the self-determined motivation in PA (β=.45, p<.001, R2=.26). Self-determined motivation in PA predicted PA intention (β=.51, p<.001, R2=.41). The predictive strength from PA intention to behavior was weak (β=.11, p=.011, R2=.21) with a statistically non-significant mediational model from self-determined motivation in PA via PA intention to PA behavior (β=.28, p=.231). This weak-to-non-significant relationship does not fully support the previous findings that have shown the feasibility of the trans-contextual model in charting the pathways from self-determined motivation in an educational context to behaviors in an out-of-school context.